2017
DOI: 10.1038/srep42386
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Photobiomodulation in the Prevention of Myocardial Ischemic Reperfusion Injury: A Systematic Review and Potential Molecular Mechanisms

Abstract: Myocardial ischemia reperfusion injury is a negative pathophysiological event that may result in cardiac cell apoptosis and is a result of coronary revascularization and cardiac intervention procedures. The resulting loss of cardiomyocyte cells and the formation of scar tissue, leads to impaired heart function, a major prognostic determinant of long-term cardiac outcomes. Photobiomodulation is a novel cardiac intervention that has displayed therapeutic effects in reducing myocardial ischemia reperfusion relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 118 publications
(213 reference statements)
4
23
0
Order By: Relevance
“…Our findings regarding the study quality of animal studies are in agreement with other animal systematic reviews which also reported lack of randomization, blinding, insufficient evidence of random housing of the animals and inappropriate statistical analysis, which are the major factors causing bias and false positive results .…”
Section: Discussionsupporting
confidence: 90%
“…Our findings regarding the study quality of animal studies are in agreement with other animal systematic reviews which also reported lack of randomization, blinding, insufficient evidence of random housing of the animals and inappropriate statistical analysis, which are the major factors causing bias and false positive results .…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have already demonstrated the therapeutic effect of low‐intensity infrared LED radiation in different IR models including hepatic injuries, skin flap ischemia, renal damage, acute myocardial infarctions, and retinal degeneration . However, none of the studies performed with different IR models focused on the effect of low‐intensity infrared LED on pain resulting from the ischemia and reperfusion procedures.…”
Section: Discussionmentioning
confidence: 99%
“…PBM, including LED and low-level laser therapy, is the low power (1-500 mW) nonthermal delivery of photons that induces a beneficial biological response in cells and tissues, 40 such as stroke 16 and traumatic brain injury. 13 PBM has been increasingly used for treatment of neuroinflammation 15 and neurodegenerative diseases.…”
Section: Led Therapy For Post-ami Vas and Neuroimmune Modulationmentioning
confidence: 99%